Socioeconomic status, sport participation, and school-related outcomes among Norwegian adolescents: a cross-sectional analysis - Grasaas, Erik; Sandbakk, Øyvind; Ostojic, Sergej; Hovrerak, May Olaug; Stea, Tonje Holte (Frontiers in Sports and Active Living, 2025)
BackgroundExtensive research highlights the critical role of sport and physical activity (PA) engagement during adolescence, as it is strongly associated with enhanced subjective well-being, reduced risk of mental health problems, and prevention of chronic diseases in adulthood. Thus, it is highly important to identify key barriers of sport participation in adolescence. The present study aimed to; (1) describe socioeconomic status (SES) across different sport disciplines among current participants and sport dropouts, (2) examine possible associations between sport participation and sport dropouts on school-related outcomes.MethodsSchool-based cross-sectional data among 90,091 adolescents aged 16–19 years were collected across Norway between 2021 and 2023. A self-report questionnaire was used to assess information about sociodemographic background, current and previous sport participation, and school-related factors, including perceived school stress, teacher care, feeling tired at school and sense of belonging at school. Adjusted binary logistic regressions were conducted using IBM SPSS Statistics.ResultsAdolescents currently participating in sport reported higher SES compared to sport dropouts (2.13 ± 0.51 vs. 1.97 ± 0.61, p < 0.01). Tennis participants demonstrated the highest SES of 2.39 ± 0.44, while motorsport participants revealed the lowest score (1.82 ± 0.49). The highest sport attrition rate (80.2%) was revealed among adolescents from the lowest SES level. Current sport participants reported favorable school-related outcomes and PA engagement compared to sport dropouts (all, p < 0.01). Adjusted logistic analyses showed that participation in sport activities was associated with lower odds of perceived school stress [OR = 0.83; 95% CI (0.81–0.86)] and being tired during school hours [OR = 0.74; 95% CI (0.71–0.77)], and higher odds for perceived teacher care [OR = 1.17; 95% CI (1.12–1.22)] and perceived sense of belonging [OR = 1.36; 95% CI (1.31–1.42)].ConclusionsHigher SES was found among adolescents participating in sport compared to sport dropouts, underscoring the importance of promoting affordable sport opportunities during adolescence. Current sport participation was associated with favorable school-related outcomes compared to sport dropouts, such as lower odds for perceived school stress and tiredness in school, and higher odds of perceived sense of belonging in school and perceived teacher care.